Efektivitas Pelaksanaan Media Sosial Dalam Strategi Pemasaran PT. Galuh Protank Logistics - Mochamad Rizky Febrian; Lia Nirawati (Politeknik Kampar, 2024)
This study aims to evaluate the effectiveness of the implementation of social media in the marketing strategy of PT. Galuh Protank Logistics. The research method used is a survey with a quantitative approach, involving 200 respondents who are customers and service users of PT. Galuh Protank Logistics. Data was collected through questionnaires distributed online. The results show that the use of social media, especially Instagram and LinkedIn, significantly increases brand awareness and customer engagement. In addition, social media has also proven to be effective in reaching a wider market and increasing sales. These findings suggest that PT. Galuh Protank Logistics must continue to optimize marketing strategies through social media to achieve maximum results. This research also provides recommendations for the development of more interesting and interactive content to increase customer engagement.